State and trait of finger tapping performance in multiple sclerosis - Gulde, Philipp; Vojta, Heike; Hermsdörfer, Joachim; Rieckmann, Peter (Scientific Reports, 2021)
Finger tapping tests have been shown feasible to assess motor performance in multiple sclerosis (MS) and were observed to be strongly associated with the estimated clinical severity of the disease. Therefore, tapping tests could be an adequate tool to assess disease status in MS. In this study we examined potential influencing factors on a maximum tapping task with the whole upper-limb for 10 s in 40 MS patients using linear mixed effects modelling. Patients were tested in three sessions with two trials per body-side per session over the course of 4–27 days of inpatient rehabilitation. Tested factors were the expanded disability scale (EDSS) score, laterality of MS, age, sex, hand dominance, time of day, session, trial (first or second), time between sessions, and the reported day form. A second model used these factors to examine the self-reported day form of patients. Linear mixed effects modelling indicated the tapping test to have a good inter-trial (proportional variance < 0.01) and inter-session reliability (non-significant; when controlling for time between sessions), an influence of hand-dominance (proportional variance 0.08), to be strongly associated with the EDSS (eta2 = 0.22, interaction with laterality of MS eta2 = 0.12) and to be not associated with the reported day form. The model explained 87% (p < 0.01) of variance in tapping performance. Lastly, we were able to observe a positive effect of neurologic inpatient rehabilitation on task performance obvious from a significant effect of the time between sessions (eta2 = 0.007; longer time spans between sessions were associated with higher increments in performance). Day form was only impacted by EDSS and the time of the day (p < 0.01, R2 = 0.57, eta2TIME = 0.017, eta2EDSS = 01.19). We conclude that the tapping test is a reliable and valid assessment tool for MS.
CRIS-Team Scopus Importer:2021-09-03